FAMOUS DIALECTOLOGY SCIENTIST - Qodirov Umarjon Akramjon o‘g‘li (Journals Park Publishing, 2025)
The article talks about the research of academician Shonazar Shoabdurakhmanov on Uzbek dialectology. His book “Uzbek Dialectology”, created in close collaboration with the Russian scientist, academician V. V. Reshetov, is carefully analyzed. It is noted that this book has been the main reference book for universities for many years and has become the main source for further scientific research.
Keywords: Shonazar Shoabdurakhmanov, dialectology, dialect, research, transcription, deafness, vowels, consonants, sound, pronunciation.